Protective effects of curcumin co-treatment in rats with establishing chronic variable stress on testis and reproductive hormones - Masoomeh Mohamadpour; Ali Noorafshan; Saied Karbalay-Doust; Tahereh Talaei-Khozani; Elham Aliabadi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Protracted and repeated exposure to chronic variable stress (CVS) may lead to reproductive dysfunction. It is a basic cause of male infertility. Curcumin (CUR) is an active fraction of turmeric that used in traditional Chinese medicine. CUR represents various pharmacological activities. Objective: The purpose of this study was to determining the effects of CUR on testis and testosterone, follicle stimulating hormone (FSH) and luteinizing hormone (LH) in rats with establishing chronic variable stress. Materials and Methods: Twenty-one adult male Sprague-Dawley rats were divided into three groups: 1) control, 2) CVS and 3) CVS+ CUR (100 mg/kg/day dissolved in 0.5 mL of olive oil). All of the animals in control, CVS, and CVS+CUR groups were sacrificed after 15 days. Testosterone, FSH, LH, and testis damage were evaluated. Results: Significant changes in the normal range of testosterone, FSH, LH serum levels and seminiferous tubule apoptotic cells were detected in CVS group compared to the control rats (p=0.02). These parameters changed to a less extent in CVS+CUR animals compared to the CVS rats (p=0.02). Conclusion: Our findings propose that curcumin might have curative potential on the reproductive system function and its impairment. It’s regulated by stress and reproductive-related hormones.